Peta Dakwah Islam Di Pontianak - Retna Dwi Estuningtiyas (INC- Islam Nusantara Center, 2021)
Pontianak with the diversity of the people who live in it and its unique culture is an area that has its own da'wah challenges. Historically, the Pontianak Sultanate was founded in 1778 led by Syarif Abdurrahman Al-Kadri, who in 1777 was assisted by Raja Haji from Riau. Attended by the Sultans and additions from Landang, Simpang, Sukadana, Malay and Mempawah, Raja Haji appointed and crowned Syarif Abdurrahman al-Kadri as Sultan of the Pontianak sultanate. After Sultan Syarif Abdurrahman AI-Kadri died in 1808 AD, successively a number of his descendant sultans came to power in the Pontianak Sultanate. The history of the Pontianak Sultanate is indeed synonymous with da'wah, struggle and sacrifice. According to the 9th Sultan of Pontianak, Syarif Abu Bakar al-Kadrie, the purpose of the establishment of the Pontianak sultanate was to strengthen the da'wah of Islamiyah. The challenges and obstacles that are felt now in the development of Islamic da'wah include the ambition of Christians in spreading their religious mission in West Kalimantan, this can be seen from several facts including, related to the Christian mission in Indonesia which is centered in Kalimantan and makes Kalimantan and Pontianak as pilot projects. short-term Christianity (2003). As for overcoming it, various Islamic da'wah strategies are needed, including: upholding ukhuwah Islamiyah; maintain the unity and integrity of the people; Cooperating in building among the Muslims themselves; Strengthening religious education in the family; Get used to being good. Pontianak dengan kemajemukan masyarakat yang tinggal di dalamnya dan keunikan budayanya merupakan wilayah yang mempunyai tantangan dakwah tersendiri. Dalam sejarahnya, Kesultanan Pontianak berdiri tahun 1778 dipimpin oleh Syarif Abdurrahman Al-Kadri, yang pada tahun 1777 dengan dibantu Raja Haji dari Riau. Dihadiri oleh para Sultan dan penambahan dari Landang, Simpang, Sukadana, Malay dan Mempawah, Raja Haji mengangkat dan menobatkan Syarif Abdurrahman al-Kadri menjadi Sultan dari kesultanan Pontianak. Setelah Sultan Syarif Abdurrahman AI-Kadri wafat tahun 1808 M, berturut-turut sejumlah sultan keturunannya berkuasa di Kesultanan Pontianak. Sejarah Kesultanan Pontianak memang identik dengan dakwah, perjuangan dan pengorbanan. Tujuan didirikannya kesultanan Pontianak sendiri, menurut Sultan Pontianak ke-9 Syarif Abu Bakar al-Kadrie, tidak lain untuk meneguhkan dakwah Islamiyah. Adapun tantangan maupun hambatan dirasakan sekarang di dalam pengembangan dakwah Islam diantaranya adalah ambisi Umat Kristiani dalam menyebarkan misi agamanya di Kalimantan Barat, hal itu terlihat dari beberapa fakta diantaranya, terkait misi Kristen di Indonesia yang dipusatkan di Kalimantan dan menjadikan Kalimantan, dan Pontianak sebagai pilot project kristenisasi jangka pendek (2003). Adapun untuk mengatasinya diperlukan beragam strategi dakwah Islam diantaranta adalah : menjunjung tinggi ukhuwah Islamiyah; menjaga persatuan dan kesatuan umat; Bekerjasama dalam membangun antar umat Islam sendiri; Menguatkan Pendidikan agama dalam keluarga; Membiasakan diri dalam kebaikan.